Pengaruh Keaktifan Belajar terhadap Prestasi Belajar Mata Pelajaran IPS Siswa Kelas Vii Di SMP Islam Raden Patah di Depok - Agung Prasteyo; Yuli Iftitah (Fakultas Syariah IAIN Laa Roiba Bogor, 2021)
ABSTRACT The purpose of this study was to discuss and analyze the Effect of Learning Activity on Learning Achievement of Social Studies Subjects for Grade VII Students at Raden Patah Islamic Middle School in Depok. This research method uses quantitative descriptive with a correlational study approach of two data variables. Data collection improves social studies learning by using a behavioral scale questionnaire consisting of 25 statements to 30 respondents. The results showed a range of Variable X data between scores 40 - 79 and dominated by class intervals 61 - 67 (40%). Overall this data interval class is above a score of 61 (80%). The mode, median and mean values ​​of the data are 62, 61, 60, respectively. The description of this data shows the number of students interacting with variable X is sufficient, but not yet optimal. Variable Y data shows the range of data between scores 8-18 and is dominated by data interval classes 14-15 (40%). Class interval data above a score of 12 is 80%. The mode, median and mean values ​​of the data are 14.4, 14.0 and 13.6, respectively. This data condition illustrates the number of students who have a significant learning achievement (80%). Data analysis showed that there was an influence (Variable X) on (Variable Y) with a correlation value of rxy = 0.757 and the results of the t-test = 6.128, whose values ​​were greater than the values ​​in Tables r and t standard. The effectiveness of using Variable X to Variable Y is 57.3% and there are other factors (42.7%) that are not yet known. Keywords: Creative Learning, Learning Achievement, Social Studies Subjects